Alloying of thin Ag and Au films on Pd(111) studied by high-resolution photoelectron spectroscopy of surface states - Fauster, Thomas; et al. (Surface Review and Letters, 1996)
Alloy formation by annealing of thin Ag and Au films on Pd(111) is studied by high-resolution ultraviolet and two-photon photoelectron spectroscopy of surface states. Changes in the composition of the top layer of the surface alloys are reflected in the energy of the surface states. Above an annealing temperature of 500 K on both systems, the crystal-induced surface state shifts continuously from the occupied state of the adsorbate to the unoccupied state of the substrate. The continuous shift reflects the variable composition of the alloys in the surface region which depends on the initial coverage and the annealing temperature. The spectroscopy of the unoccupied image states permits the investigation of growth and morphology of deposited metal layers. Three-dimensional island growth, layer-by-layer growth, and surface alloy formation with metastable surface configurations and diffusion of the overlayer material into the bulk are identified.